The influence of conventional heating method on physicochemical properties of Malaysian stingless bee honey - Wan Nadja, Julika; Azilah, Ajit; Aishath, Naila; Nur Suhana, .; Ahmad Ziad, Sulaiman (AIP Publishing, 2022)
The application of conventional heating in commercial honey is necessary however it can be damaging especially to the physicochemical and nutritional properties of honey if it was subjected to excessive temperature. Thus, this present research aimed to study the effect of conventional heating method towards physicochemical properties of Malaysian stingless bee honey where pH, moisture content, hydroxymethylfurfural, diastase activity and sugar profile were evaluated. The stingless bee honey samples from two main species in Malaysia namely, Heterotrigona Itama and Geniotrigona Itama and two commercially obtained stingless bee honey were heated at 40 ℃, 50 ℃, 63 ℃ and 90 ℃ for 30 min in water bath. The analyses showed that all honey samples pH was reduced significantly at 90 ℃ and the moisture content was effectively reduced by 20% which is favorable to avoid fermentation and slowing crystallization in honey. Besides that, the sugars values also slightly decreased with increasing temperature. Both commercial honey has high HMF (84.0 – 159.4 mg/kg) and low diastase number (3.17-3.58 DN) prior to heating which implying that these honey has been exposed to high temperature before packaging. After heat was applied, HMF content increased (40.3 to 216.8 mg/kg) while diastase activity (1.47 to 5.21 DN) decreased gradually indicating both parameters are very sensitive to heat. In conclusion, the ideal temperature for heating using conventional method should be no more than 90 ℃ so that the quality of honey can still be preserved.